Home‐Visiting Support for New Mothers With Additional Vulnerabilities: A Qualitative Inquiry Identifying Barriers to Implementation. - Tracey, Danielle; Nash, Simone; Burns, Elaine; Nivedita, Raut (Health & Social Care in the Community, 2026)
Home‐visiting support has been cast as one of the most effective ways to reach new mothers with additional vulnerabilities and is instrumental in preventing adverse outcomes for mothers, children, and families. Whilst the body of empirical evidence for the efficacy of home‐visiting support is strong, less is known about barriers to successful implementation. In this qualitative study, we interviewed 47 adults with diverse experience of a home‐visiting service (22 mothers, 15 volunteers, 6 staff, 3 external professionals and one partner of a service user) to capture a comprehensive understanding of potential implementation barriers. Findings reveal that both individual and organisational factors may undermine implementation which could subsequently jeopardise the realisation of service benefits. Factors include limited availability of volunteers and coordinators, as well as poor volunteer‐mother fit, and shame and guilt felt by mothers. Recommendations for a tiered approach to strengthen implementation are provided.